FORMATION OF AMMONIA IN A LINEAR PLASMA REACTOR - FILEP, E.; KENÉZ, L.; KUTASI, N.; FERENCZ, L. (Studia Universitatis Babeș-Bolyai Physica, 2016)
A study of ammonia formation in DC plasma discharge is presented in function of gas composition and working temperature by using a laboratory scale plasma nitriding reactor. The nitriding process took place in case of a Hollow Cathode (HC) configuration with treated part on Anodic Potential (HCAPN). It was found that in the temperature range of 500-700 K the yield of ammonia was directly proportional with the discharge current and the coefficient of efficiency was found to be constant. This indicates that ammonia formation in low temperature plasma discharge is electrochemical in nature. During our experiments nitride layers was formed on both the cathode and the inner anode. This indicates that the neutral ammonia molecules have a nitrogen carrying role in the plasma nitriding process.